Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1159/000519643
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Sacubitril/Valsartan in Maintenance Hemodialysis Patients with Heart Failure

Abstract: <b><i>Background:</i></b> Heart failure (HF) is one of the main comorbidities in patients receiving maintenance hemodialysis (HD). Sacubitril/valsartan (SAC/VAL) is widely used in HF patients with reduced ejection fraction (HFrEF) or HF mid-range ejection fraction (HFmrEF). However, the pharmacokinetic (PK) and pharmacodynamic properties of SAC/VAL in HD patients with HF remain uncertain. <b><i>Objectives:</i></b> This study aimed to analyze the efficacy and PK p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“… B-blocker: n = 16, CCB: n = 5, ACEI/ARB: n = 0, MCA: n = 2 Feng et al. , 27 2022 China 2019–2020 Prospective, observational, self-controlled study 50–100 mg twice a day 18 mo 11 Median 50 (IQR 39–72) 5 (45%) HD HFrEF and HFmrEF, LVEF 40% and 40–50% N/A Fu et al. , 28 2021 China 2018–2019 Retrospective, observational self-controlled study 50–100 mg twice a day 3–12 mo 21 Median 55 (IQR 38–61) 14 (67%) PD HFpEF, LVEF >50% Hypertension: n = 21, Diabetes: n = 5, CAD: n = 21 B-blocker: n = 11, CCB: n = 21, ACEI/ARB: n = 6, Diuretic: n = 10 Guo et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… B-blocker: n = 16, CCB: n = 5, ACEI/ARB: n = 0, MCA: n = 2 Feng et al. , 27 2022 China 2019–2020 Prospective, observational, self-controlled study 50–100 mg twice a day 18 mo 11 Median 50 (IQR 39–72) 5 (45%) HD HFrEF and HFmrEF, LVEF 40% and 40–50% N/A Fu et al. , 28 2021 China 2018–2019 Retrospective, observational self-controlled study 50–100 mg twice a day 3–12 mo 21 Median 55 (IQR 38–61) 14 (67%) PD HFpEF, LVEF >50% Hypertension: n = 21, Diabetes: n = 5, CAD: n = 21 B-blocker: n = 11, CCB: n = 21, ACEI/ARB: n = 6, Diuretic: n = 10 Guo et al.…”
Section: Resultsmentioning
confidence: 99%
“…Change of LVEF was evaluated in a total of 9 studies. 13 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 36 The duration of follow-up ranged from 3 to 18 months (refer to Table 1 for details). All of these studies were before and after studies and reported LVEF at baseline and after the intervention in the same group of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Sacubitrilat, the active metabolite of the prodrug sacubitril, and valsartan were not removed by dialysis filtration, but their levels remained within the safe ranges on the interdialytic interval days. Moreover, S/V up to 100 mg twice daily was safe and associated with a significant improvement in EF and reductions in NT‐proBNP and hsTnT (all P < 0.05) in HF patients undergoing haemodialysis 75 …”
Section: Efficacy and Safety In Subgroups Of Interestmentioning
confidence: 92%
“…Moreover, S/V up to 100 mg twice daily was safe and associated with a significant improvement in EF and reductions in NT-proBNP and hsTnT (all P < 0.05) in HF patients undergoing haemodialysis. 75…”
Section: Safety In Chronic Kidney Disease Patientsmentioning
confidence: 99%
“…Therefore, in patients with heart failure, directly initiating ARNI can avoid the treatment delay caused by initial ACEI intake followed by a switch to ARNI. The 2021 US expert consensus on the management of patients with HFrEF states that ARNI should be preferred over ACEI/ARB for patients with HFrEF ( 74 ).…”
Section: Use Of Arni In Non-dialysis Patients With Ckdmentioning
confidence: 99%